Memprediksi Perilaku Whistleblowing Melalui Machiavellianism: Studi Perilaku Whistleblowing di Twitter Pada Mahasiswa Anggota Organisasi Intra Kampus Perspektif Ekonomi Islam - Pramesti, Faradita Agenovindia; Nuzulia, Siti (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to determine the influence between machiavellian personality and whistleblowing intentions on whistleblowing behavior in the form of retweets on reporting news threads on Twitter with whistleblower intentions. This research is a quasi-experiment with 154 research participants who actively use the Twitter application. Participants were asked to give a reaction to a thread. Whistleblower behavior is seen from the behavior of participants who retweet and quote retweet the threads sent by the researcher. The results of this study indicate that machiavellian personality does not directly affect whistleblowing behavior in the form of retweets and quote retweets. However, whistleblowing intention has an influence on whistleblowing behavior in the form of retweets and quote retweets. It is suspected that the types of posts that are not directly related to the interests of people with machiavellian personality make them not show whistleblowing behavior.